2004
DOI: 10.1073/pnas.0402764101
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in ClpC2/Hsp100 suppress the requirement for FtsH in thylakoid membrane biogenesis

Abstract: The Arabidopsis var2 variegation mutant defines a nuclear gene for a chloroplast FtsH metalloprotease. Leaf variegation is expressed only in homozygous recessive plants. The cells in the green leaf sectors of this mutant contain morphologically normal chloroplasts, whereas cells in the white sectors contain abnormal plastids lacking organized lamellar structures. var2 mutants are hypersusceptible to photoinhibition, and VAR2 degrades unassembled polypeptides and is involved in the D1 repair cycle of photosyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
78
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(83 citation statements)
references
References 46 publications
(53 reference statements)
3
78
2
Order By: Relevance
“…Recently, the GreenCut2 signaling protein At2g48070 (CrCPLD33) was shown to mediate the chloroplast oxidative burst, which is part of the plant's immune response (76). Other types of chloroplast-nucleus signaling pathways mediated by GreenCut2 proteins might include coordination of plastid division during the cell cycle, modulation of the synthesis of thylakoid membranes (77,78), and control of the stoichiometry of photosynthetic complexes within those membranes.…”
Section: Functional Meta-analysis Of Domains and Activitiesmentioning
confidence: 99%
“…Recently, the GreenCut2 signaling protein At2g48070 (CrCPLD33) was shown to mediate the chloroplast oxidative burst, which is part of the plant's immune response (76). Other types of chloroplast-nucleus signaling pathways mediated by GreenCut2 proteins might include coordination of plastid division during the cell cycle, modulation of the synthesis of thylakoid membranes (77,78), and control of the stoichiometry of photosynthetic complexes within those membranes.…”
Section: Functional Meta-analysis Of Domains and Activitiesmentioning
confidence: 99%
“…The observed suppression of leaf variegation by fug1 and clpc2 is similar in this sense. Park and Rodermel (2004) have reported that mutation or inactivation of ClpC2, a subunit comprising an ATPase complex of the Clp protease, leads to a suppression of variegation in var2. Loss of ClpC2 itself does not cause any visible phenotype, whereas loss of another isomer ClpC1 results in the decrease of Fv/Fm and a chlorotic phenotype (Sjö gren et al, 2004;Clarke et al, 2005;Kovacheva et al, 2005).…”
Section: Suppressors Of Leaf Variegation and Evolutional Implicationmentioning
confidence: 99%
“…Indeed, the screening of var2 suppressors has been successfully performed by Park and Rodermel (2004), suggesting that several recessive mutations exist. In this study, we focused on one of the var2 suppressors that was isolated by our forward genetics screen.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in otp70, the splicing of rpoC1 is compromised, which also leads to abnormal plastidencoded plastid RNA polymerase activities (18). In addition to these two categories of genes, virescent mutants have also been observed at rather high frequency in our screens for yellow variegated (var2) suppressors (19). One such suppressor line, ems2505, defines a leaky allele of an essential gene coding for a novel chloroplast protein that is indispensable for chloroplast development and plant survival (20).…”
mentioning
confidence: 99%